A Stretchable Electrochemical Sensor for Inducing and Monitoring Cell Mechanotransduction in Real Time. Issue 32 (6th July 2017) - Liu, Yan‐Ling; Qin, Yu; Jin, Zi‐He; Hu, Xue‐Bo; Chen, Miao‐Miao; Liu, Rong; Amatore, Christian; Huang, Wei‐Hua
Abstract: Existing methods offer little direct and real‐time information about stretch‐triggered biochemical responses during cell mechanotransduction. A novel stretchable electrochemical sensor is reported that takes advantage of a hierarchical percolation network of carbon nanotubes and gold nanotubes (CNT‐AuNT). This hybrid nanostructure provides the sensor with excellent time‐reproducible mechanical and electrochemical performances while granting very good cellular compatibility, making it perfectly apt to induce and monitor simultaneously transient biochemical signals. This is validated by monitoring stretch‐induced transient release of small signaling molecules by both endothelial and epithelial cells cultured on this sensor and submitted to stretching strains of different intensities. This work demonstrates that the hybrid CNT‐AuNT platform offers a versatile and highly sensitive way to characterize and quantify short‐time mechanotransduction responses. Abstract : Cell stretching : A stretchable electrochemical sensor with excellent mechanical and electrochemical behavior and very good cellular compatibility has been developed. Transient biochemical signals during cell mechanotransduction can be induced and monitored in real time. This work offers a powerful platform to characterize and quantify mechanotransduction responses from mechanically sensitive cells.